The Socialist Economics of Karl Marx and His Followers - Veblen, Thorstein (Quarterly Journal of Economics, 1906)
Journal Article The Socialist Economics of Karl Marx and his Followers Get access Thorstein Veblen Thorstein Veblen University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 20, Issue 4, August 1906, Pages 575–595, https://doi.org/10.2307/1882722 Published: 01 August 1906